2015
DOI: 10.1242/jeb.114140
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic burst locomotion by hydroplaning and paddling in common eiders (Somateria mollissima)

Abstract: Common eiders (Somateria mollissima) are heavy sea-ducks that spend a large portion of their time swimming at the water surface. Surface swimming generates a bow and hull wave that can constructively interfere and produce wave drag. The speed at which the wavelengths of these waves equal the waterline length of the swimming animal is the hull speed. To increase surface swimming speed beyond the hull speed, an animal must overtake the bow wave. This study found two distinct behaviors that eider ducks used to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 46 publications
0
9
0
2
Order By: Relevance
“…Although characterizing the contributions of the wings and tail to aquatic takeoff is beyond the scope of the current study, they are clearly key to achieving vertical takeoff in mallards. In fact, the wings and feet working in unison is a common strategy for birds moving at the water's surface and has been described for behaviors like taxiing prior to takeoff or paddle-assisted flight (Norberg and Norberg, 1971;Gough et al, 2015), and hydroplaning and/or steaming (Aigeldinger and Fish, 1995;Gough et al, 2015). An inverse dynamics study pairing ground reaction forces (measured using a force plate) and fluid dynamic forces (measured using PIV), although challenging to carry out, could elucidate the relative contributions of the hindlimbs, wings and tail during takeoff.…”
Section: Implications Of Moving Between Water and Landmentioning
confidence: 99%
See 1 more Smart Citation
“…Although characterizing the contributions of the wings and tail to aquatic takeoff is beyond the scope of the current study, they are clearly key to achieving vertical takeoff in mallards. In fact, the wings and feet working in unison is a common strategy for birds moving at the water's surface and has been described for behaviors like taxiing prior to takeoff or paddle-assisted flight (Norberg and Norberg, 1971;Gough et al, 2015), and hydroplaning and/or steaming (Aigeldinger and Fish, 1995;Gough et al, 2015). An inverse dynamics study pairing ground reaction forces (measured using a force plate) and fluid dynamic forces (measured using PIV), although challenging to carry out, could elucidate the relative contributions of the hindlimbs, wings and tail during takeoff.…”
Section: Implications Of Moving Between Water and Landmentioning
confidence: 99%
“…Previous work on terrestrial takeoff has examined takeoffs from solid surfaces by focusing on distal hindlimb kinematics and substrate reaction forces (Earls, 2000;Tobalske et al, 2004;Berg and Biewener, 2010;Provini et al, 2012b;Chin and Lentink, 2017;Crandell et al, 2018) or wing musculature (Williamson et al, 2001). Others have considered avian behaviors at the water's surface, including paddle-assisted flight (Norberg and Norberg, 1971;Gough et al, 2015), mating displays (Clifton et al, 2015), hydroplaning (Aigeldinger and Fish, 1995) and steaming (Gough et al, 2015). However, no previous studies have examined how vertical takeoff varies between water and land, and none have reported hindlimb muscle function or the kinematics of proximal joints (hip and knee) during takeoff.…”
Section: Introductionmentioning
confidence: 99%
“…However, surface tension could still affect performance by adding partial weight support or by decreasing drag. We found that the skin of the geckos in our study is superhydrophobic (contact angle a = 138.4 ± 2.5 ; n = 20; Figure S3) independent of location, and therefore might decrease drag through mechanisms that rely on high surface tension at the skin-water interface [26,30,31].…”
Section: Surface-tension Forcesmentioning
confidence: 85%
“…Unlike most surface-swimming vertebrates [17,24], interfacial locomotion of rapidly moving geckos on pure water exceeded hull speed up to a factor of two or more. Above Froude numbers of 1.0, animals can skim on the water's surface by hydroplaning, generating hydrodynamic lift as the body is inclined with a positive trim angle [23,30]. Between Froude numbers of 0.6 to 1.0, animals are supported by both hydrodynamic and hydrostatic (buoyant) forces, a strategy known as semi-planing.…”
Section: Semi-planing and Hydrodynamic Lift Forcesmentioning
confidence: 99%
“…(también observado en Somateria, Gough et al 2015). Los movimientos subacuáticos de Somateria y los movimientos de steaming son realizados con las alas plegadas, independientemente de su tamaño, por lo cual no se descarta que Cayaoa hubiera podido realizarlos de modo análogo.…”
Section: Miembros Anterioresunclassified